ATUAÇÃO INTERNACIONAL DE SALVADOR: UMA ANÁLISE CRÍTICA DAS AÇÕES INTERNACIONAIS DA PREFEITURA DE SALVADOR DE 2001 A 2008 - Santana, Helena Francisca Ribeiro de Araújo (2010)
This work represents an additional effort toward understanding the contemporaneous phenomenon of the search for an autonomous international action undertaken by local governments, non-central entities of the federalist system, emphasizing the case of Salvador during the period ranging from 2001 to 2008. The analysis carries out a comparative study of the international actions assumed during Mayor Imbassahy s second term (2001-2004) and Mayor João Henrique s first term (2005-2008), pointing out differences between those terms, specifically due to the creation of SECRI International Relations, which is an administrative-organizational agency of the Salvador City Hall for the international relations (2005). In this sense, it is discussed, within a critical perspective, the role played by the participation of cities in the international scene, the motivations that guide them towards being internationally active and the implications that stem from these actions, specifically for the city of Salvador. Furthermore, technical, political, economic, social and legal aspects of this sort of international action are also discussed. Some possibilities within the practice of the internationalization of local governments which go beyond the nearly exclusive focus of the academic literature on foreign trade and international negotiations are presented. There is an attempt to rescue the historical context of the international actions carried out by Salvador and to highlight aspects of the political and economical recent situation that have motivated the intensification of its international acting through the institutionalization of its international department in 2005 through SECRI International Relations. Understanding the ideological background of this practice and the motivations involved in its institutionalization process, its change from SECRI International Relations to International Relations Advisory Department make up the object of study hereby proposed.